The effectiveness of different model statement variants for eliciting information and cues to deceit - Leal, Sharon (Legal and criminological psychology, 2022)
Background According to previous research, the use of a model statement results in both truth tellers and lie tellers reporting a similar amount of extra information than the instruction to be detailed. We examined (1) whether level of engagement with attending to the model statement affects the veracity findings and (2) whether valuable details is a diagnostic veracity indicator. Method We created four model statement variants, two had lower levels of engagement and two had higher levels of engagement with attending to the model statement content. Participants were allocated to one of these four conditions or to the no model statement control condition. Results Participants in one of the higher engagement conditions recalled the model statement content significantly better than participants in one of the lower engagement conditions. The audio model statement and the face-to-face model statement resulted in more information than the no model statement control condition. In none of the model statement conditions did total details emerge as a veracity indicator; valuable details did not yield the expected effect either. Conclusion A model statement serves as an eliciting information tool and the amount of additional information is similar among truth tellers and lie tellers.